Mechanism of Increased LDL (Low-Density Lipoprotein) and Decreased Triglycerides With SGLT2 (Sodium-Glucose Cotransporter 2) Inhibition. Issue 9 (September 2018) - Basu, Debapriya; Huggins, Lesley-Ann; Scerbo, Diego; Obunike, Joseph; Mullick, Adam E.; Rothenberg, Paul L.; Di Prospero, Nicholas A.; Eckel, Robert H.; Goldberg, Ira J.
Abstract : Objective—: SGLT2 (sodium-glucose cotransporter 2) inhibition in humans leads to increased levels of LDL (low-density lipoprotein) cholesterol and decreased levels of plasma triglyceride. Recent studies, however, have shown this therapy to lower cardiovascular mortality. In this study, we aimed to determine how SGLT2 inhibition alters circulating lipoproteins. Approach and Results—: We used a mouse model expressing human CETP (cholesteryl ester transfer protein) and human ApoB100 (apolipoprotein B100) to determine how SGLT2 inhibition alters plasma lipoprotein metabolism. The mice were fed a high-fat diet and then were made partially insulin deficient using streptozotocin. SGLT2 was inhibited using a specific antisense oligonucleotide or canagliflozin, a clinically available oral SGLT2 inhibitor. Inhibition of SGLT2 increased circulating levels of LDL cholesterol and reduced plasma triglyceride levels. SGLT2 inhibition was associated with increased LpL (lipoprotein lipase) activity in the postheparin plasma, decreased postprandial lipemia, and faster clearance of radiolabeled VLDL (very-LDL) from circulation. Additionally, SGLT2 inhibition delayed turnover of labeled LDL from circulation. Conclusions—: Our studies in diabetic CETP-ApoB100 transgenic mice recapitulate many of the changes in circulating lipids found with SGLT2 inhibition therapy in humans and suggest that the increased LDL cholesterol found with this therapy is because of reduced clearance of LDL from the circulation and greater lipolysis of triglyceride-rich lipoproteins. Most prominent effects of SGLT2 inhibition in the current mouse model were seen with antisense oligonucleotides-mediated knockdown of SGLT2. Abstract : Supplemental Digital Content is available in the text.